A Neutral and Aromatic Boron‐Rich Inorganic Benzene. Issue 16 (26th February 2020) - Ota, Kei; Kinjo, Rei
Abstract: A neutral 1, 4‐diaza‐2, 3, 5, 6‐tetraborinine derivative (3 ) featuring a 6π ring system has been synthesized and structurally characterized. The prospective aromatic nature of 3 was assessed by single‐crystal X‐ray analysis, NMR, and UV/Vis absorption spectroscopy as well as computational studies. Furthermore, preliminary reactivity investigations showed that 3 does not only react with diphenyl acetylene but also readily captures CO2 in a [4+2] cycloaddition under ambient conditions. Abstract : Who needs carbon anyway? A purely inorganic benzene derivative based on a six‐membered B4 N2 ring has been synthesized. Structural features associated with computational studies indicate a pronounced aromatic nature concomitant with a considerable delocalization of six π‐electrons at the B4 N2 ring. The molecule readily undergoes a [4+2] cycloaddition with unsaturated molecules under ambient conditions.